2022
DOI: 10.1101/2022.08.07.503115
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Virological characteristics of the SARS-CoV-2 Omicron BA.2.75

Abstract: SARS-CoV-2 Omicron BA.2.75 emerged in May 2022. BA.2.75 is a BA.2 descendant but is phylogenetically different from BA.5, the currently predominant BA.2 descendant. Here, we showed that the effective reproduction number of BA.2.75 is greater than that of BA.5. While the sensitivity of BA.2.75 to vaccination- and BA.1/2 breakthrough infection-induced humoral immunity was comparable to that of BA.2, the immunogenicity of BA.2.75 was different from that of BA.2 and BA.5. Three clinically-available antiviral drugs… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
36
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 93 publications
(325 reference statements)
5
36
0
2
Order By: Relevance
“…Limitations of this study include a relatively small sample size for the boosted health care workers and the utilization of pseudotyped lentivirus for the neutralization assay rather than an authentic virus assay. However, our results for neutralization resistance are in accordance with several recent preprints (Cao et al, 2022; Gruell et al, 2022; Saito et al, 2022; Sheward et al, 2022; Wang et al, 2022b; Xie et al, 2022; Yamasoba et al, 2022a). Additionally, the lentiviral psedotype neutralization assay has been previously validated by assays with authentic SARS-CoV-2 (Zeng et al, 2020), and confirmed by numerous laboratories in the field.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Limitations of this study include a relatively small sample size for the boosted health care workers and the utilization of pseudotyped lentivirus for the neutralization assay rather than an authentic virus assay. However, our results for neutralization resistance are in accordance with several recent preprints (Cao et al, 2022; Gruell et al, 2022; Saito et al, 2022; Sheward et al, 2022; Wang et al, 2022b; Xie et al, 2022; Yamasoba et al, 2022a). Additionally, the lentiviral psedotype neutralization assay has been previously validated by assays with authentic SARS-CoV-2 (Zeng et al, 2020), and confirmed by numerous laboratories in the field.…”
Section: Discussionsupporting
confidence: 93%
“…We further demonstrate that BA.2.75 exhibits enhanced S-mediated cell-cell fusion compared to BA.2, albeit to a lesser extent than BA.4/5. This enhanced triggering of BA.2.75 Smediated fusion may reflect improved receptor utilization that is not present in earlier Omicron subvariants, consistent with several recent preprints (Cao et al, 2022;Saito et al, 2022;Wang et al, 2022a). Critically, we find that the N460K mutation present in BA.2.75 is essential for the enhanced fusion phenotype.…”
Section: Discussionsupporting
confidence: 87%
“…The reason for this is unclear; however, it might be due to differences in the binding affinity of the S protein for hACE2 among BA.1, BA.2, BA.4, BA.5, and BA.2.75. Recent studies have reported that the RBD of BA.2.75 exhibits higher binding affinity for the hACE2 receptor than that of BA.2 and BA.4/5 (Cao et al, 2022;Saito et al, 2022). SARS-CoV-2 enters cells in two distinct ways: by fusion of the viral lipid envelope with the target cell plasma membrane or fusion of the viral envelope with the endosomal membrane after internalization through the endocytic pathway (Hoffmann et al, 2020;Jackson et al, 2022;Walls et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Although our analysis of vaccinee sera was limited to a single post-booster timepoint, our results and those of others suggest that antibody escape is an overall less pronounced characteristic of BA.2.75 compared with BA.4/5. 7 , 8 , 9 Thus, additional features favouring viral expansion beyond vaccine escape might be required for BA.2.75 to gain a growth advantage over BA.4/5.…”
mentioning
confidence: 99%